Disintegrins extracted from totonacan rattlesnake (Crotalus totonacus) venom and their anti-adhesive and anti-migration effects on MDA-MB-231 and HMEC-1 cells - Rivas Mercado, Eric Abdel; Neri Castro, E.; Bénard Valle, M.; Rucavado Romero, A.; Olvera Rodríguez, A.; Zamudio Zuñiga, F.; Alagón Cano, A.; Garza Ocañas, Lourdes (2020)
Disintegrins are low molecular weight cysteine-rich proteins (4–14 kDa) that are isolated mainly from viperid snake venom. Due to their potential as lead compounds for binding and blocking integrin receptors, snake venom disintegrins have become one of the most studied venom protein families. The aim of this study was to obtain disintegrins from C. totonacus venom and evaluate their capability to bind and block integrin receptors. The C. totonacus disintegrin fraction (totonacin) represents two disintegrin isoforms obtained from C. totonacus venom. These disintegrins showed extracellular-matrix (ECM) protein adhesion and migration inhibitory effects on MDA-MB-231 and HMEC-1 cells. Totonacin (3 μM) inhibited MDA-MB-231 cell adhesion to the ECM proteins, fibronectin, vitronectin, and laminin by 31.2, 44.0, and 32.1, respectively. Adhesion inhibition to fibronectin, vitronectin, and laminin observed on HMEC-1 cells was 42.8, 60.8, and 51%, respectively. In addition, totonacin (3 μM) significantly inhibited MDA-MB-231 and HMEC-1 cell migration (41.4 and 48.3%, respectively). Totonacin showed more potent cell adhesion inhibitory activity toward vitronectin in both cell lines. These results suggest a major affinity of totonacin toward αVβ3, α8β1, αVβ5, αVβ1, and αIIbβ3 integrins. In addition, the inhibitory effect observed on MDA-MB-231 and HMEC-1 cell migration reinforces the evidence of an interaction between these disintegrins and αVβ3 integrin, which plays a key role in migration and angiogenesis.